Pricing TIPS and treasuries with linear regressions - Michael Abrahams; Tobias Adrian; Richard K. Crump; Emanuel Moench (Federal Reserve Bank of New York, 2012)
We present an affine term structure model for the joint pricing of Treasury Inflation-Protected Securities (TIPS) and Treasury yield curves that adjusts for TIPS' relative illiquidity. Our estimation using linear regressions is computationally very fast and can accommodate unspanned factors. The baseline specification with six principal components extracted from Treasury and TIPS yields, in combination with a liquidity factor, generates negligibly small pricing errors for both real and nominal yields. Model-implied expected inflation provides a better prediction of actual inflation than breakeven inflation. The value of the deflation floor calculated from the model is generally small in magnitude, but spiked during the recent crisis.
Keywords: G12; E44; 330; TIPS; inflation expectations; affine term structure models